PEMBINAAN USAHA KECIL MENENGAH PADA DINAS KOPERASI USAHA KECIL DAN MENENGAH, PERINDUSTRIAN DAN PERDAGANGAN DI KABUPATEN KEPULAUAN MENTAWAI - Yenni Jufri; Naufal Raid; Donna Ikranova F; Bahef Yesi (Jurnal Public Administration, Business and Rural Develoment Planning, 2019)
His study discusses coaching conducted by the Office of Cooperatives of Small and Medium Enterprises, Trade and Industry of the Mentawai Islands Regency on Small and Medium Enterprises. As is known, cooperatives and SMEs are an integral part of the national business world that has a very important purpose and role in economic development. Mentawai Islands Regency is one of the regencies located in West Sumatra Province, formed under RI Law No.49 of 1999, the district consists of 4 islands namely Siberut Island, Sipora Island, North Pagai Island and South Pagai Island. In addition there are several small islands. Over the years the development of SMEs in the Mentawai Islands Regency has increased. With this increase, the participation of the government, both local and central government, is needed to further increase the growth of the number of SMEs in improving the economy. But along with the development of SMEs in the Mentawai Islands Regency, other coaching such as counseling and training has not been evenly distributed. Counseling and training of SMEs is only done by the department of SMEs which are deemed necessary to do the counseling and training, not all SMEs in the Mentawai Islands Regency